EFEKTIFITAS KOMUNIKASI INTERPERSONAL TERHADAP KEHARMONISAN RUMAH TANGGA PASANGAN BEDA AGAMA DESA KALIPANG KECAMATAN GROGOL KABUPATEN KEDIRI - Akhmad Fitra Fatkhur Rokhmansyah , (Mediakita, 2021)
Interpersonal communication is needed by interfaith couples as an effort to maintain relationships so that this couple's marriage lasts. There are several elements of communication that can be used to maintain relationships, besides there are also ways and types of maintaining relationships. This article aims to determine and explain the influence of interpersonal communication in the households of interfaith couples in Kalibago Hamlet, Kalipang Village, Grogol District, Kediri Regency. By using a case study approach. In-depth interview method for extracting data with interview guidelines aimed at informants of interfaith family couples. The resource persons were determined using a purpose sampling technique with a qualitative phenomenological approach. The results of the study indicate that there are couples who are able to live a lasting life by using ways to uphold the value of honesty, openness and providing support to each partner who has different religions and beliefs, and children are considered as a couple's goal to maintain their harmonious relationship. Meanwhile, the type of interpersonal communication that is often developed is face-to-face communication.